Fast‐moving diffuse auroral patches: A new aspect of daytime Pc3 auroral pulsations. Issue 2 (2nd February 2017) - Motoba, Tetsuo; Ebihara, Yusuke; Kadokura, Akira; Engebretson, Mark J.; Lessard, Marc R.; Weatherwax, Allan T.; Gerrard, Andrew J.
Abstract: Auroral pulsations are a convenient diagnostic of wave‐particle interactions in the magnetosphere. A case study of a daytime Pc3 (22–100 mHz) auroral pulsation event, measured with a ~2 Hz sampling all‐sky camera at South Pole Station (74.4°S magnetic latitude) on 17 May 2012, is presented. The daytime Pc3 auroral pulsations were most active in a closed field line region where the aurora was dominated by diffuse green‐line emissions and within ±2 h of magnetic local noon. Usually, but not always, the corresponding periodic variations were recorded with a colocated search coil magnetometer. Of particular interest is the two‐dimensional auroral signature, indicating that the temporal luminosity variations at a given point were due to repeated formation and horizontal motion of faint, nonpulsating auroral patches with scale sizes of ~100 km. The individual patches propagated equatorward with speeds of 15 km s −1 up to 20–25 km s −1 one after another along the magnetic meridian through local magnetic zenith. These properties differ considerably from typical pulsating aurorae, being periodic on‐off luminosity variations in a particular auroral patch and drifting in accordance with the convection electric field in the magnetosphere. We speculate that such repetitive patterns of the fast‐moving auroral patches, being another aspect of the daytime Pc3 auroral pulsations, may be a visible manifestation of compressional Pc3 waves which propagate earthward and cause modulation of precipitating keV electron fluxes in the dayside outer magnetosphere. Key Points: Daytime Pc3 auroral pulsations occurred over South Pole Station, Antarctica The auroral pulsations result from repetitive episodes of fast‐moving diffuse auroral patches The spatiotemporal behavior of the auroral patches may be a visible manifestation of compressional Pc3 waves in the outer magnetosphere